Taxonomical study of species Zygophyllum fabago L. in Iraq. - Baghdad Science Journal (مجلة بغداد للعلوم)
The present study dealt with taxonomic characters of species Zygophyllum fabago L. in Iraq . this study included the exo-morphological characters which indicated that the species was sub-shrub with solid stem and swallow nodes ,with compound bifoliate and stipulate leaves, the flower is complete and perfect with clawed petals . stamen colored with scaly appendage , fruit capsule with ribs . Anatomical study of vegetative parts indicate that the sclerenchymal tissue was very diffuse in stem such as fibers and sclerides ( stone cells ) , the leaves were bifacial . The geographical distiribution of the species plants was studied . The results supported with photographs